PENGARUH PENGETAHUAN INVESTASI DAN PENDAPATAN TERHADAP MINAT BERINVESTASI REKSADANA SYARIAH DENGAN PERILAKU KEUANGAN SEBAGAI VARIABEL MODERASI - Rendrayana, Ezra Reanita; Haqim, Luqman (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Islamic mutual funds are a forum for collecting funds from the public which will then be placed in an investment portfolio into various securities in the capital market which must comply with the rules and principles of sharia, of course still bound by the OJK. This study aims to determine the effect of investment knowledge and income on interest in investing in Islamic mutual funds with financial behavior as a moderating variable. This type of research is quantitative research with research subjects, namely active students of FEB / FEBI / DDKBD of state universities in Surabaya City who are members of the investment gallery totaling 110 students. The sampling technique used purposive sampling with non probability sampling method. The data collection technique used was a questionnaire with googleform as the respondent's data collection instrument. Data analysis techniques using multiple linear regression analysis and Moderated Regression Analysis (MRA) with SPSS 25 software. The results showed (1) investment knowledge has a significant positive effect on interest in investing in Islamic mutual funds; (2) income has a significant positive effect on interest in investing in Islamic mutual funds; (3) financial behavior cannot moderate the effect of investment knowledge on interest in investing in Islamic mutual funds; (4) financial behavior cannot moderate the effect of income on interest in investing in Islamic mutual funds